The nature, frequency and value of stimulation induced seizures during extraoperative cortical stimulation for functional mapping. (October 2020) - Spilioti, Martha; Winston, Joel S.; Centeno, Maria; Scott, Catherine; Chowdhury, Fahmida; Diehl, Beate
Highlights: Electroclinical SIS were observed approximately in a quarter of patients who had extraoperative CS for functional cortical mapping. SIS were habitual just over half of the time (56%). In three-quarters of patients who had habitual SIS, the location of contacts eliciting habitual SIS originated from the same location as the spontaneous ictal onset zone in icEEG. Abstract: Purpose: The aim of this retrospective service evaluation was to determine the nature, frequency and clinical value of seizure occurrence during extraoperative direct cortical stimulation for functional mapping in patients undergoing invasive recordings (icEEG) for epilepsy surgery workup. Methods: We reviewed 145 sequential cases of patients with refractory focal epilepsy who underwent intracranial electrode implantation and extraoperative direct cortical stimulation (CS) for functional mapping. CS intended for mapping can elicit as a by-product electrical or electroclinical events, such as afterdischarges, subclinical EEG seizures, and stimulation-induced seizures (SIS). SIS may have habitual or non-habitual semiology (as defined by comparison to the patient's spontaneous events). Results: In our cohort, electrical (subclinical EEG seizures) or electroclinical events, (SIS) were recorded in 34.5% (50/145) patients during CS. SIS occurred in 23.4% (34/145) of all patients, of which over half were habitual SIS (SIShab ). In most cases the location of contacts eliciting habitual SIS originated from the same location as the spontaneous ictal onset zone in icEEG. Of those with SIS hab undergoing surgery (n = 13), seizure freedom was achieved in 61.5%, and of those with SISNH undergoing surgery (n = 10), 40% became seizure free (ns). Conclusions: Electroclinical SIS occur in about a quarter of CS for functional mapping; SIS are habitual in the majority of cases, and where elicited, SIS in icEEG could be an additional diagnostic tool to localize the seizure onset zone. However, a significant minority of stimulations lead to non-habitual SIS.